DIGITAL TURN OF MATERIAL OBJECTS IN THE TEXTUAL WORKS OF DIGITAL HERMENEUTIC - UYSAL, Dudu (SSD Journal, 2022)
Since the beginning of the 21st century, the digital turn of new media such as computers and the Internet has significantly impacted the traditional humanities and hermeneutics. When the traditional humanities are updated as the digital humanities, the traditional hermeneutics are also updated as digital. Disciplines such as literary studies and philology turn into digital literary studies and computer philology. Digital texts also replace printed ones because the literary and philological information obtained from digital textual works has a significant function as an essential competence of digital interpretation. At this point, the material objects of the printed textual works appear as immaterial objects of the digital media. The material and non-material impacts of the print media and the digital media on the textual works of digital interpretation in digital literary studies and computer philology are dealt with as the central topic of this work. Finally, answers are searched for these questions: Are the methods of traditional interpretation directly incorporated into the practices of digital hermeneutics? Or are the forms of digital interpretation determined independently of the methods of traditional hermeneutics according to the properties of digital media?